RANCANGANÂ UNDANGâ€UNDANGÂ KESETARAANÂ DANÂ KEADILANÂ GENDERÂ (RUUÂ KKG)Â DALAMÂ TINJAUANÂ MAQASHIDÂ ASYâ€SYARIâ€™AH - Amilia, Fatma (Musawa Jurnal Studi Gender dan Islam, 2012)
Maqashid Asy-Syariâ€™ah is an extraordinary method to view and develop Islamic ideas and spirit in many circumstances. It is often used as an analytical knife to solve problems and the application of Islamic law. This Article will attempt to read and analyze the Draft Law on Gender Equality through this method. The existence of this yet unsanctioned law has raised controversy. But such controversies should instead be used as materials to revise and perfect the draft law instead of a reason to reject it outright. The result of the analysis of the draft law shows that it generally contains the values of Islamic law. However, it is undeniable that there are several mistakes and errors which must be discussed to be perfected. The decisionÂ  whether to issue the law should depend on a costbenefit analysis.